2008
DOI: 10.1210/jc.2007-1403
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Tricuspid Regurgitation in Patients with Prolactinomas Chronically Treated with Cabergoline

Abstract: Moderate tricuspid regurgitation is more frequent in patients taking cabergoline (at higher cumulative doses) than in de novo patients and control subjects, but the clinical significance of this finding has not been established. A complete echocardiographic assessment is indicated in patients treated long term with cabergoline, particularly in those requiring elevated doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
125
8
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 37 publications
8
125
8
6
Order By: Relevance
“…Subsequently, there were several studies addressing the risk of valvar damage in prolactinoma and acromegaly patients, without clear evidence of clinically significant valvar disease [12,[40][41][42]. The majority of the studies evaluated patients treated for hyperprolactinemia, and the follow-up times were short to assure that CAB was not associated with a risk for valvar disease in the doses used in acromegaly treatment [40,41,43,44]. In addition, acromegaly itself is associated with valvar disease [45][46][47], and there are some anecdotal reports of valvar damage associated with CAB therapy in acromegaly [48].…”
Section: Side Effectsmentioning
confidence: 99%
“…Subsequently, there were several studies addressing the risk of valvar damage in prolactinoma and acromegaly patients, without clear evidence of clinically significant valvar disease [12,[40][41][42]. The majority of the studies evaluated patients treated for hyperprolactinemia, and the follow-up times were short to assure that CAB was not associated with a risk for valvar disease in the doses used in acromegaly treatment [40,41,43,44]. In addition, acromegaly itself is associated with valvar disease [45][46][47], and there are some anecdotal reports of valvar damage associated with CAB therapy in acromegaly [48].…”
Section: Side Effectsmentioning
confidence: 99%
“…After the publication of the papers, which showed an increased risk of valve regurgitation after treatment with pergolide and cabergoline in patients with Parkinson's disease, six cross-sectional studies have evaluated the association between valve regurgitation and the use of cabergoline in patients treated for prolactinoma, including the study by Wakil et al published in this edition of the European Journal of Endocrinology (Table 1) (10)(11)(12)(13)(14)(15). These studies included a total of 413 patients, treated with cabergoline for 45-79 months.…”
Section: Introductionmentioning
confidence: 99%
“…Cabergoline, which possesses a complete 5HT 2b agonistic activity, is the drug of choice in the treatment of prolactinomas, but the results of observational studies investigating the risk of FVHD in these patients are still controversial. Some of them have reported no relevant findings (8,9,10,11,12), five trials have observed clinically insignificant valvular changes (13,14,15,16,17), and only one study has reported an increased prevalence of moderate tricuspid regurgitation with a cumulative dose-dependent risk (18). Published data on the potential profibrotic effect of bromocriptine, a partial 5HT 2b agonist, are exclusively limited (19).…”
Section: Introductionmentioning
confidence: 99%